High strength and antifouling metakaolin-based ceramic membrane for juice clarification - Hubadillah, Siti Khadijah; Othman, Mohd Hafiz Dzarfan; Harun, Zawati; Jamalludin, Mohd Riduan; Mohd Zahar, Mohd Izzat Iqbal; Ismail, Ahmad Fauzi; A. Rahman, Mukhlis; Jaafar, Juhana (Springer Nature, 2018)
Key lime, watermelon, and kiwifruit juices were successfully clarified by using a novel high strength and antifouling metakaolinbased ceramic membranes prepared via combination of phase inversion and sintering technique. The fabricated membrane was characterized by utilizing scanning electron microscopy (SEM) analysis, three-point bending strength, juice permeation, and fouling behavior analysis. In this work, the fouling behavior of the membrane was studied using Darcy’s law for cross-flow filtration system. Analysis of the fouling mechanism revealed that the membranes’ fouling was most influenced by the cake filtration mechanism and can be solved easily by applying high operating pressure. Membranes prepared at a sintering temperature of 1300 °C were found to be optimum membranes for juice clarification as it possessed excellent mechanical strength (176.8 MPa) and pure water flux of 273 L/m2 h at 500 kPa. Interestingly, it was also found that the membrane could endure high operating pressure up to 700 kPa, which consequently solved the fouling issue. Thereby, the precious juice properties, such as total suspended solid (TSS), pH, acidity, and density for all juices, were found to be almost unaffected.